1998
DOI: 10.1002/(sici)1098-1136(199809)24:1<39::aid-glia5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular calcium waves in glia

Abstract: Glial cells are capable of communicating increases in [Ca 2ϩ ] i from a single cell to many surrounding cells. These intercellular Ca 2ϩ waves have been observed in glia in multiple different preparations, including dissociated brain cell cultures, glial cell lines, organotypic brain slice cultures, and intact retinal preparations. They may occur spontaneously, or in response to a variety of stimuli. Ca 2ϩ waves occurring under different conditions in different preparations may have distinctive patterns of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 49 publications
8
131
0
1
Order By: Relevance
“…These data suggest that a messenger or messengers are released from cells in zone 1 after an increase in [C a 2ϩ ] i , and this messenger or messengers diff use across the void region and activate cells located in zone 2. The arrow in f denotes the time at which the cell in zone 1 was mechanically stimulated and corresponds to t ϭ 0 sec for the sequence of ratio images in a. communication between cells, there is increasing evidence that extracellular Ca 2ϩ signaling might also play a role in intercellular Ca 2ϩ waves in glia (Charles, 1998;Cotrina et al, 1998;Guthrie et al, 1999). Indeed in this study, we observed increases in [Ca 2ϩ ] i (Fig.…”
Section: Intercellular Ca 2؉ Waves Induced By Mechanical Stimulation supporting
confidence: 50%
See 1 more Smart Citation
“…These data suggest that a messenger or messengers are released from cells in zone 1 after an increase in [C a 2ϩ ] i , and this messenger or messengers diff use across the void region and activate cells located in zone 2. The arrow in f denotes the time at which the cell in zone 1 was mechanically stimulated and corresponds to t ϭ 0 sec for the sequence of ratio images in a. communication between cells, there is increasing evidence that extracellular Ca 2ϩ signaling might also play a role in intercellular Ca 2ϩ waves in glia (Charles, 1998;Cotrina et al, 1998;Guthrie et al, 1999). Indeed in this study, we observed increases in [Ca 2ϩ ] i (Fig.…”
Section: Intercellular Ca 2؉ Waves Induced By Mechanical Stimulation supporting
confidence: 50%
“…One generally accepted mode of intercellular Ca 2ϩ wave propagation involves the diffusion of Ca 2ϩ mobilizing second messengers, including inositol-1,4,5-trisphosphate (IP 3 ) and Ca 2ϩ , across gap junctions (Nedergaard, 1994;Charles, 1998). Extracellular, gap junction-independent modes of Ca 2ϩ signaling, involving the release of a diffusible messengers, also appear to operate in this particular system however, with ATP release from cells and P 2 receptor-coupled elevation of [Ca 2ϩ ] i having recently been suggested as a likely candidate (Cotrina et al, 1998;Guthrie et al, 1999).…”
Section: Abstract: Nitric Oxide; Glia; Calcium Waves; Mobilization; mentioning
confidence: 99%
“…However, there is growing evidence that astrocytes play an active role in neuronal excitability and synaptic function Araque et al, 1999;Parri et al, 2001). Given that the spatial and temporal characteristics of intercellular Ca 2ϩ waves in astrocytes are very similar to those of spreading depression, the spreading oligemia of migraine, and the spread of some types of seizures (Charles, 1998), it is appealing to speculate that extracellular Ca 2ϩ and Mg 2ϩ may be involved in these phenomena via their effects on astrocyte Ca 2ϩ signaling and ATP release. Modulation of astrocyte signaling represents a novel potential mechanism by which extracellular divalent cations influence the function of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte Ca 2ϩ waves may occur spontaneously or may be evoked by a variety of stimuli including mechanical stimulation, electrical stimulation, or neurotransmitters (Charles, 1998). In addition to being a pathway for communication among astrocytes, Ca 2ϩ waves have been shown to be a pathway for bidirectional signaling between astrocytes and multiple other cell types, including neurons (Araque et al, 1998;Kang et al, 1998;Parri et al, 2001), microglia (Schipke et al, 2002), and vascular endothelial cells (Leybaert et al, 1998;Paemeleire and Leybaert, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…ronal and glial depolarization 31,32 . CSD triggers a series of cellular and molecular events, eventually resulting in massive surges of extracellular potassium and intracellular calcium.…”
Section: Mechanisms Of Association Putative Mechanisms Commentsmentioning
confidence: 99%